Evaluation of Delay Causes for BOT Projects Based on Perceptions of Different Stakeholders in Turkey - Budayan, Cenk (ASCE-AMER SOC CIVIL ENGINEERS, 2019)
Because delays are common in construction projects, causes of delays are widely investigated in the construction-management literature. However, there is no consensus on the relative severity of various causes of delay because severity may change with respect to project characteristics, such as the type of project and/or procurement type. Public-private partnership (PPP) has been utilized extensively in recent years, and the number of public construction works worldwide that adopted the PPP has increased gradually. However, the delay causes specific to PPPs have not been investigated deeply. Moreover, the perceptions of different stakeholders on causes of delay in PPP projects have never been investigated, although the perception difference between stakeholders is considered an important issue in delay management. In this study, the perceptions of three key stakeholdersnamely, consultants, the private sector, and the public sectoron delay causes in build-operate-transfer (BOT) projects performed in Turkey, which is one of the leading countries in terms of number of PPP projects and the total value of PPP projects, were investigated. The delay causes specific to BOT projects were evaluated by conducting a workshop to determine the causes of delay in the Turkish market. The identified delay causes were evaluated using the analytical hierarchical process (AHP) by 11 participants who represent consultants, the private sector, and the public sector. The correlations between the respondents were evaluated using Pearson's correlation coefficient and Spearman's rank correlation coefficient. This study showed that the most important delay causes are related to the uncertainties and changes. In particular, private sector participants emphasized the importance of certainty on political and governmental issues and minimization of changes in design to avoid delays in BOT projects. In contrast, the respondents from the public sector proposed that a detailed feasibility study and preliminary plan should be prepared and the transfer stage should be planned carefully. Finally, different perceptions were observed among the stakeholders at the stages where the collaboration of the stakeholders is limited.
Keywords: Delay analysis; Build-operate-transfer projects; Public-private partnership; Analytical hierarchical process; Turkey; PUBLIC-PRIVATE PARTNERSHIPS; CRITICAL SUCCESS FACTORS; ANALYTIC HIERARCHY PROCESS; INFRASTRUCTURE PROJECTS; HONG-KONG; PPP PROJECTS; CONSTRUCTION PROJECTS; DEVELOPING-COUNTRIES; RISK ALLOCATION; PROCESS AHP; Engineering